Rogues' gallery: The full freedom of the Bianchi CMB anomalies - Pontzen, A (2009)
Combining a recent derivation of the CMB evolution equations for homogeneous but anisotropic (Bianchi) cosmologies with an account of the full linearized dynamical freedoms available in such models, I calculate and discuss the various temperature and polarization anisotropy patterns that may be formed. Certain anisotropies can be hidden in superhorizon modes at early times, thus avoiding any constraints from nucleosynthesis, while nevertheless producing nontrivial redshift-zero temperature patterns in flat and open universes. The results are likely to be more of pedagogical than observational interest, but future work will assess whether such patterns can be matched to anomalies in WMAP results. © 2009 The American Physical Society.